The Conditions That Promote or Discourage Physical Punishment as Described by Taiwanese and Taiwanese American Mothers. (May 2020) - Lin, Joyce
Physical punishment and the conditions that promote and discourage its use were explored in a sample of Taiwan-born mothers living in Taiwan ( n = 19) and the United States ( n = 15), and U.S.-born Taiwanese American mothers ( n = 15). Grounded theory was used to extract themes from focus group transcriptions. Mothers from all groups indicated that they preferred a variety of nonphysical methods to correct their children's misbehaviors. U.S.-born mothers were less likely to report use of violent/forceful physical punishment than the other two groups. Some conditions were associated with mothers' use of physical punishment, such as holding traditional gender beliefs, believing in filial piety and familism, having experienced physical punishment, receiving support from others for physical punishment, experiencing physical punishment as being effective for one's child, and having a male child. However, other conditions were associated with the rejection of physical punishment, including believing in saving face or the stereotype that physical punishment is illegal in the United States, having personally experienced physical punishment as negative, having experienced nonphysical discipline/punishment, experiencing physical punishment of one's child as ineffective, and experiencing regret from physical punishment use. Conditions related to physical punishment use and rejection ranged from distal to proximal, and these independently and interactively influenced choices to use physical punishment or not. Findings emphasize the complexity of caregivers' decisions to use or reject physical punishment, underscoring both maternal experiences and cultural contributions, and highlighting areas that researchers and interventionists may further explore to reduce the use of physical punishment.